Ideas and not solutions: Enabling innovation through internal crowdsourcing in the Tata Group - KOTHA, Reddi (Institutional Knowledge at Singapore Management University, 2023)
Ravi Arora, Vice President (Group Innovation), Tata Sons Private Limited, and his Group Innovation team initially faced difficulty when introducing the concept of open innovation to the Tata Group. They tried to ease the staff into embracing it by getting them to share problem statements, learn from other companies which had already adopted it, and form InnoClusters among Tata companies which collaborated in diverse areas. The team subsequently organised monthly thematic eHackathons in which staff could propose ideas to solve business challenges on specific themes posted by senior management. In the course of organising the eHackathons, Ravi’s team encountered several issues such as administrative difficulties and mismatched expectations. The central question in this case study is whether eHackathons and internal crowdsourcing in general are employee engagement devices or serious initiatives by organisations to obtain solutions to innovation problems. The question centres around the number of ideas that become full-fledged solutions, since only very few, less that 10 percent, are actually implemented. This begs the question of whether employee sourcing of ideas can ever be an effective source of innovative solutions. Hence the case is titled ‘ideas and not solutions’ to reflect this vast chasm between idea generation and solution implementation, while still celebrating the winners from each eHackathon. The case can be used in innovation-related courses to do with open innovation at the undergraduate or postgraduate level. Case discussion will enable students to evaluate the merits of focusing on ideas for internal innovation challenges, explore ways to turn ideas into solutions, analyse the implications of innovation challenge winners coming from outside the unit that posted these challenges, and appraise the role of rewards in spurring participation in internal innovation challenges.